2022
DOI: 10.1016/j.gim.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Reverse phenotyping facilitates disease allele calling in exome sequencing of patients with CAKUT

Abstract: Congenital anomalies of the kidneys and urinary tract (CAKUT) constitute the leading cause of chronic kidney disease in children. In total, 174 monogenic causes of isolated or syndromic CAKUT are known. However, syndromic features may be overlooked when the initial clinical diagnosis of CAKUT is made. We hypothesized that the yield of a molecular genetic diagnosis by exome sequencing (ES) can be increased by applying reverse phenotyping, by re-examining the case for signs/symptoms of the suspected clinical syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…Current data indicates that when a patient presents with CAKUT, genetic testing will reveal a monogenic cause of disease in 10%-20% of individuals (Mann, Braun, et al, 2019;Rasmussen et al, 2018;Seltzsam et al, 2022;van der Ven, Connaughton, et al, 2018;Weber et al, 2006). This percentages increases in the presence of extra-renal features of disease and in patients with so-called syndromic CAKUT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current data indicates that when a patient presents with CAKUT, genetic testing will reveal a monogenic cause of disease in 10%-20% of individuals (Mann, Braun, et al, 2019;Rasmussen et al, 2018;Seltzsam et al, 2022;van der Ven, Connaughton, et al, 2018;Weber et al, 2006). This percentages increases in the presence of extra-renal features of disease and in patients with so-called syndromic CAKUT.…”
Section: Discussionmentioning
confidence: 99%
“…In a Korean population of children with CAKUT, targeted exome sequencing identified genetic causes for 13.8% of the 94 pathogenic variants in either HNF1B , PAX2 , EYA1 , UPK3A , and FRAS1 (Ahn et al, 2020). More recently, we demonstrated that in a large cohort of 731 families with CAKUT, a single‐gene cause for CAKUT was identified in 11.4% of families (Seltzsam et al, 2022). Copy number variants (CNVs) result from either deletions or duplications of chromosomal regions.…”
Section: Monogenic Causation In Cakutmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse genetics (i.e., reframing clinical diagnosis in view of genetic results) and identification of phenocopies have already proved efficacious in guiding this process in other fields of nephrology (e.g., podocytopathies and steroid-resistant nephrotic syndrome, ciliopathies, congenital anomalies of the kidney and urinary tract, etc.) [ 33 , 34 , 35 ], paving the way for a profound revision of disease ontology. Previous studies reported on disease reclassification based on reverse genetics, including in tubulopathies [ 14 , 18 , 28 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Denn sie ermöglicht ein Reverse-Phenotyping und so ein gezieltes Suchen nach syndromaler Beteiligung. Beispielsweise könnte so aus einer „unspezifischen fokal-segmentalen Glomerulosklerose (FSGS)“ eine „ PAX2 -assoziierte Nephropathie mit Netzhautkolobom“ werden, was die klinische Versorgung entsprechend verändert und die Prognose nach Nierentransplantation deutlich verbessert 7 , 8 .…”
Section: Extrarenale Fehlbildungen Bei Cakutunclassified